Sufism’ Channels of Communication in Contemporary Era - Putro, Zaenal Abidin Eko; Nurhayati, Ida; Utami, Pradiptia Wulan (UI Scholars Hub, 2019)
It is widely known that Sufi order group (kelompok tarekat) has grown in many areas of Indonesia since the influx on Islam in archipelago several centuries ago. The religious group is currently still persistence elsewhere in Indonesia until nowadays. Usually, a Sufi order member has a special obligation to recite some sort of Quranic verses given by their Sufi teacher. Generally, the goal they want to achieve by joining sufi order is to calm their mind over worldly problems. Here, this is the importance to look at how they communicate with one another, especially delivering a message from the teacher to the member. In the rising of Islam of the Archipelago discourses (Islam Nusantara) among scholars as well as the undergo modernization within the Muslim community, the existence of the Sufi order needs to be more explained. Data from the research show that the persistent of this group is a result from continuously transferring tenets from the old generation to new generations one. In this regard, it is reasonable to see that channels of communication are very much used in this group so that they could still exist today. This article is steamed from qualitative research aiming at studying channels of communication operated in Sufi order group. Overall, although Sufi order is regarded as a rather traditional group, but its adaptation and adoption to modern communication technology could help it to continue its existence until the contemporary era.